Role of the Wound, Ostomy and Continence Nurse in Stoma Care: the Patient’s Opinion (Estima – Brazilian Journal of Enterostomal Therapy, 2013)
The wound, ostomy and continence (WOC) nurse is a professional who has the knowledge and training in the care of persons with a stoma. A WOC nurse should develop skills to promote patient self-care behaviors, which favor a rapid reintegration of these patients, thus improving their quality of life. The aim of this study was to assess the ostomy patient’s opinion about the care received from the WOC nurse during the rehabilitation process. This was a quantitative, exploratory, descriptive study conducted with 40 ostomy patients registered for at least 6 months in a center of care and services for the ostomy patient, in the city of São Paulo, Brazil. Data were collected using a 9-item questionnaire. We found that 36 (90%) patients had knowledge about the role of the WOC nurse and considered the WOC nurse’s interventions as “very necessary”, and that only 4 (10%) patients regarded the interventions as “necessary”. Thirty-nine (97%) patients were satisfied with the performance of the WOC nurse in the health center. The results showed that the WOC nurse seems to play a fundamental role in the care of ostomy patients as the main responsible for the health education and encouragement of ostomy patients toward self-care after the stoma creation. However, it is still necessary to expand the nurse’s role in all levels of care for ostomy patients.